Kranialines elektrostimuliacijos poveikis sportininku atsigavimui po ivairaus intensyvumo fiziniu kruviu - Rudzitis, A.; Larins, V.; Chupriks, L.; Zhilinskis, L.; Chuprika, A. (Sporto Mokslas-Sport Science, 2015)
The purpose of the research was to detect the effect of Cranial Electrical Stimulation (CES) on athletes in general and under different load intensity in their practice body recovery process quality. Optimal restoring of athletes` body capacity under loads of training and competition processes is as essential as optimal choice of physical and psychological loads in practice.